Gender aspects of small-scale private irrigation in Africa - van Koppen, Barbara; Hope, Lesley; Colenbrander, W. (International Water Management Institute, 2012)
This Working Paper presents methodological and substantive findings of gender-differentiated quantitative farm household surveys about smallholders? private irrigation technology adoption in Ghana and Zambia. Focusing on three gender variables, household headship, labor provision and plot management, the paper examines adoption rates, types of technologies and gendered labor provision in female- and male-headed households; compares adoption rates on women?s own plots with overall rates; compares women?s decision-making on irrigated plots and rainfed plots; and examines impacts of targeting strategies. Findings suggest that women are proactive irrigation adopters in spite of the many obstacles they face. Removing those obstacles serves both gender equality and irrigation policies.